2003
DOI: 10.1148/rg.235035031
|View full text |Cite
|
Sign up to set email alerts
|

US of Liver Transplants: Normal and Abnormal

Abstract: Whole-liver transplantation is an accepted and successful method of treating end-stage liver disease. As a result of the shortage of cadaveric livers, split-liver transplantation and living donor liver transplantation are becoming more commonplace. Ultrasonography (US) is the initial imaging modality of choice for detection and follow-up of early and delayed complications from all types of liver transplantation. Vascular complications include thrombosis and stenosis of the hepatic artery, portal vein, or infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
185
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(196 citation statements)
references
References 48 publications
1
185
0
10
Order By: Relevance
“…Multiple studies have shown that metabolic syndrome increases after transplant, especially in adult patients. 1,4 Reasons for increased rates of metabolic syndrome in transplant patients include being overweight and the adverse effects of immunosuppressive drugs. Multiple studies have shown the effects of metabolic syndrome on adulthood diseases, with increased cardiovascular complications (increased by 10 times) and type 2 DM (increased by 4 times).…”
Section: Farzad Vafaei Et Al/experimental and Clinical Transplantatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that metabolic syndrome increases after transplant, especially in adult patients. 1,4 Reasons for increased rates of metabolic syndrome in transplant patients include being overweight and the adverse effects of immunosuppressive drugs. Multiple studies have shown the effects of metabolic syndrome on adulthood diseases, with increased cardiovascular complications (increased by 10 times) and type 2 DM (increased by 4 times).…”
Section: Farzad Vafaei Et Al/experimental and Clinical Transplantatiomentioning
confidence: 99%
“…1 A return to ordinary lifestyle activities with normalized hypermetabolic state (versus that seen with liver insufficiency) and normal diet can cause progressive weight gain in these patients. [2][3][4] Determination of the predisposing factors contributing to mortality in patients with progressive liver insufficiency remains a challenging issue. In addition, determining the optimal time for transplant and the effective factors on short-term and long-term survival are debatable topics in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported sensitivity of Doppler US for the detection of hepatic artery stenosis is 80%-90% (Abbasoglu et al, 1997;Crossin et al, 2003;Kok et al, 1998). Spectral broadening and focal accelerated velocity greater than 2 m/sec (Crossin et al, 2003;Nghiem et al, 1996;Platt et al, 1997) at the site of arterial anastomosis indicate stenosis. However, the site of narrowing is often difficult to identify by US due to overlying bowel gas especially in conduit graft, and the diagnosis is usually made on the basis of the Doppler US findings obtained distal to the stenosis.…”
Section: Hepatic Artery Stenosismentioning
confidence: 99%
“…The value of Doppler ultrasonography in the early diagnosis of vascular complications after liver transplant has been previously established. 1,2 However, the immediate changes in the splanchnic hemodynamics after graft perfusion and the physiologic changes during graft recovery are still under debate. 3 Few reports have investigated early graft hemodynamics by using Doppler ultrasonography after LDLT, with hemodynamics with LDLT influenced by the complex vascular anastomosis and small graft volume compared with deceased-donor liver transplant (DDLT).…”
Section: Introductionmentioning
confidence: 99%